Analisis perhitungan, penyetoran dan pelaporan Pajak Penghasilan Pasal 22 atas pengadaan barang pada Balai Pengujian dan Penerapan Mutu Hasil Perikanan Bitung - Lintang, Chikita Thasya; Sabijono , Harijanto; Rondonuwu , Sintje (Riset Akuntansi dan Portofolio Investasi, 2024)
Income Tax Article 22 (PPh Article 22) is a form of withholding or collection of tax carried out by one party against the taxpayer and is related to goods trading activities. The aim of the research is to determine the Calculation, Deposit and Reporting of Article 22 Income Tax on Procurement of Goods at the Testing Center and Implementation of the Quality of Bitung Fishery Products. The data analysis method used is the descriptive analysis method. The results of this research show that there are still errors in calculating and collecting PPh Article 22. Payments for income tax article 22 are made via the North Sulawesi Province KASDA application, but first create a billing code created by the UPTD treasurer via the tax e-billing application, but it is still there is a delay in depositing PPh Article 22, and in reporting income tax article 22 using the SPT made through the application